Genetic variation and asymmetry in populations of Iphigenia brasiliensis (Lamarck, 1818) from different localities and environments. Issue 1 (10th January 2019) - Bonner, A.; Ferreira, M. S. N.; Duarte, M. R.; Silva, E. P.
ABSTRACT: Iphigenia brasiliensis (Lamarck, 1818) is a species of bivalve of the family Donacidae Fleming, 1828 which inhabits unconsolidated substrata and occurs in Brazil between 0°07ʹ04ʺS, 49°23ʹ17ʺW and 29º19ʹ46ʺS, 49º42ʹ39ʺW, and is also found in Florida (USA), Suriname and parts of the Caribbean sea. As an estuarine species it is subject to a wide range of environmental variables usually presenting considerable variation in morphological traits and genetic composition. In this paper, the presence and type of asymmetry in the species was inferred based on measures from left and right valves and genetic variation was assessed by means of allozymes electrophoresis. The assessment of levels of asymmetry and genetic variation was done in three different localities and two environments (Channel and Mangrove). The results indicate the generalized presence of asymmetry, which varied between directional (DA) and fluctuating (FA) depending on the environment. Associations between FA and genetic variation were statistically significant on the dependence of the measure assessed. Thus, we present information on the levels of asymmetry and genetic variation of natural populations of I. brasiliensis which may be useful to research and management of this species.